Kepuasan Masyarakat Terhadap Pelayanan Polisi Sektor Bawang Kabupaten Banjarnegara - Sumino, Sumino; Sutrischastini, Ary (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2017)
This research objectives to understand how big citizen’s satisfaction on Bhabinkamtibnas’ service officers in build Kamtibnas in Polsek Bawang Banjarnegara area. Respondents taken as many as 100 people as samples by the method Accidental sampling. Interviews and surveys was the method that used in data collection. Anlaysis method used on this research was SERVQUAL method.This research have five dimension SERVQUAL, there are tangible, Reliable, Responsiveness, Assurance, dan empathy. The results are overall of each attributes dimensions SERVQUAL still negative and has an average gap by -0.36. This shows that Bhabinkamtibnas’ service officers still didn’t meet the citizen satisfactory. Despite the value of gap very small (under 1), this indicates that Bhabinkamtibnas’ service officers still need to improve its quality to reach the ideal services.